Integrasi spasial informalitas dalam ruang perkotaan di Jakarta - Ruth Dea Juwita; Yohanes Basuki Dwisusanto (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Urban informality is an everyday life phenomenon in Jakarta but has not been extensively discussed, especially in relation to spatial design practice. This is important because formality and informality are not entirely separate but rather interconnected and complementary (Moatasim, 2019). It has also been discovered that on-street informality such as street vending demonstrates the existence and trend of urban space and also acts as the most visible manifestation of the informal economy. Therefore, this research focuses on investigating the integration of urban informality with special attention to its influence on the spatial or architectural aspects. This was achieved through the qualitative method which involves the application of a phenomenological paradigm by participating in the street vending and informal economy on Thamrin 10, Jalan H. Agus Salim, and Jalan Percetakan Negara streets in Jakarta. The results showed that informality is present at different degrees of contemporary urban life and there is a pressing spatial demand for such activities. Moreover, it was discovered that spatial integration of urban informality has the ability to sustain and catalyse greater urban frameworks, including the activities of the formal sector.